Does screening for physical and psychosocial symptoms vary between medical oncology treatment centres?. Issue 5 (14th September 2015) - Zucca, Alison; Sanson‐Fisher, Rob; Waller, Amy; Carey, Mariko; Boyes, Allison W.; Proietto, Anthony
Abstract: Objective: Our aim is to examine whether provider screening for physical and emotional symptoms, as reported by medical oncology outpatients, varies across medical oncology treatment centres. Methods: A cross‐sectional sample of 716 patients attending the outpatient medical oncology department of six public cancer treatment centres across five Australian states participated. Four patient‐report survey items explored how often patients were specifically asked by clinical staff at the treatment centre about their (i) emotional distress (anxiety, distress and depression), (ii) pain, (iii) fatigue and (iv) other physical symptoms (e.g. nausea and constipation). Asking at less than half of all appointments was classified as infrequent screening. Results: No significant associations were found between treatment centre and symptom screening for emotional distress ( p = 0.65), pain ( p = 0.21), fatigue ( p = 0.95) and other physical symptoms ( p = 0.40). The proportion of patients who were regularly screened versus infrequently screened was significantly higher for physical symptoms than emotional symptoms ( p < 0.001): 36% infrequently screened for emotional distress (range: 33–45%), 15% infrequently screened for pain (range: 9–21%), 16% infrequently screened for fatigue (range: 15–19%) and 11% infrequently screened for other physical symptoms (range: 5–17%). Conclusions: No significant variation in symptom screening was found across treatment centres. While the majority of patients received recommended care, treatment centres must continue to improve symptom screening rates, particularly for emotional distress. However, screening is only the first step and must be accompanied by the offer of help and provision of help to relieve patient suffering. Copyright © 2015 John Wiley & Sons, Ltd.